Incidence of social and political factors in the ambient environment of the Puno (Peru) Regional Government - Tumi Quispe, Jesús E. (2018)
The study analyzed the social and political factors that affect the prioritization of environmental investment in the management of the regional government of Puno. The research design was non-experimental, transversal, documentary and quantitative of a descriptive nature; the unit of analysis was made up of the leaders of civil society organizations and the authorities and officials of the regional government. The operational population, determined at random, considering the 95% degree of confidence and margin of error of 0.05, was 160 executives from civil society. The data collection, in the core, was carried out through a survey applied in the year 2017, whose processing and systematization was in the statistical software SPSS. The results induce that the investment in the environmental agenda in the regional public management of Puno is conditioned by the articulation of the strategic and programmatic orientations established by the concerted regional development plan (PDRC) and the environmental institutionality that assign it a substantial priority in environmental investment; With the initiatives and demands of local authorities and civil society organizations and the political will of regional authorities, given its pragmatic perspective and short-term vision, investment in strategic environmental projects is minimal and not significant, which is evident in the process of formulation and implementation of the participatory budget.